Solation of Citric Acid from Microorganisms - Sattarov Abdumurod Sattarovich; Boltaeva Surayyo Jora qizi; Kamolova Nilufar Normomin qizi; Odilova Shahnoza Hayrullaevna (Researchparks Publishing, 2022)
Citric acid is widely used in medicine, food, chemical and light industries. According to the data, the world production of citric acid is 400 thousand tons per year. This article describes the fermentation steps in citric acid production, industrial synthesis, shallow culture, and liquid culture.